PELATIHAN PEMASARAN ONLINE (E-COMMERCE) UNTUK MENINGKATKAN PENJUALAN PADA KAMPUNG OPAK PANDEGLANG - Kurniawanto, Hadi; Auliana, Sigit; Kusuma, Jaka Wijaya; Suhandi, Suhandi; Muhandri, Tjahja; Suyatma, Nugraha Edi (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2024)
The aim of this training is to increase the knowledge and skills of partners, in this case the group of opak craftsmen, farmer groups and teenagers from the Al-Barokah Mosque, located in the Waqf Village, Sukaratu Village, Majasari Pandeglang District, Banten, in implementing marketing of opak products using information technology-based marketing. online (e-commerce). The methods used in this training are: socialization, application of information technology, online-based marketing training and assistance (e-commerce), evaluation and monitoring. The results of this training show that the target partners: opak craftsmen groups, farmer groups and mosque youth, 50% can implement online marketing (e-commerce) through social media (WA, Facebook, Instagram), waqf opak websites and increase opak sales by around 50% - 80 %